2022
DOI: 10.1109/jstars.2022.3170073
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for Road Surface Roughness Estimation Using Airborne Polarimetric SAR

Abstract: The road surface roughness is an important parameter that determines the quality of a road network. It has a direct influence on the grip and skid resistance of the vehicles. For this reason, this parameter has to be periodically monitored to keep track of its changes. Nowadays, road surface roughness is measured by driving measurement vehicles equipped with laser scanners all over the country. But, this approach is very costly, labor-intensive, and time-consuming. This article is done to evaluate the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The SAR polarimetry-based models [17] and the Oh models [18], [19] used in the literature for roughness estimation require the cross-polarization channels and hence cannot be used for road surface roughness estimation. The remaining models that require only the co-polarization channels are the semi-empirical Dubois model [20] and the modified Dubois model specifically developed for the road surface roughness estimation [24]. In [24], it was shown that the Dubois model has an incidence angle dependency and cannot estimate the roughness changes between concrete and asphalt surfaces at steeper incidence angles, which led to the development of the modified Dubois model for road surface roughness estimation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SAR polarimetry-based models [17] and the Oh models [18], [19] used in the literature for roughness estimation require the cross-polarization channels and hence cannot be used for road surface roughness estimation. The remaining models that require only the co-polarization channels are the semi-empirical Dubois model [20] and the modified Dubois model specifically developed for the road surface roughness estimation [24]. In [24], it was shown that the Dubois model has an incidence angle dependency and cannot estimate the roughness changes between concrete and asphalt surfaces at steeper incidence angles, which led to the development of the modified Dubois model for road surface roughness estimation.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, no GT data are available for the secondary test sites. Therefore, the surface roughness results obtained from these test sites can only be compared to the results obtained from the surface roughness estimation models investigated in previous work [5], [24], [27].…”
Section: Test Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…To meet this challenge, it is necessary to propose an efficient and real-time observation system to discover the road surface potholes. For this purpose, several methods can be used to observe damaged road sections rapidly, including laser scanning methods [9]- [10] (3D laser scanning), machine vision (stereo machine vision) [12]- [14], airborne Synthetic Aperture Radar (SAR) [15], Ground Penetrating Radar [16], and vibration [17].…”
Section: Introductionmentioning
confidence: 99%